Pharmacological therapy of acute heart failure: what is available now and what is expected in future - A. A. Eremenko (Вестник анестезиологии и реаниматологии)
The objective: to present an overview of current approaches to pharmacological therapy of acute heart failure (AHF).Results: the discussion focuses on drugs that are currently available and being actively studied in ongoing clinical trials. Disadvantages and adverse reactions of modern medications for the treatment of AHF are presented. Vasodilators cannot be used for arterial hypotension; inotropic drugs (catecholamines and phosphodiesterase inhibitors) produce proarrhythmogenic effect, increase the myocardial oxygen demand, and may cause excessive vasodilation. The mortality in patients receiving these medications and vasopressor agents remains high. The article presents data on the positive hemodynamic effect of levosimendan calcium sensitizer in patients with severe heart failure, as well as in some other categories of cardiac surgery patients but it emphasizes that the attitude to its effect on long-term survival of patients remains ambiguous. To remove contradictions, it is necessary to conduct the trial that is properly designed and does not contradict the indications and contraindications noted in the instructions for its use. It is suggested that in such trials, in particular, it is advisable to use temporary endpoints of the trial that are comparable to the duration of action of the studied drugs. In the nearest future, data will be obtained that will allow evaluating the possibility of wide clinical use of new groups of drugs: cardiac myosin activators, natriuretic peptides, vasopressin receptor inhibitors, drugs that affect the expression of calcium ATPase in the cardiac sarcoplasmic network (SERCA2a), including those developed using genetically engineered technologies.